Influência dos glicocorticóides na lesão pulmonar aguda de ratos submetidos à sepse - Garcia, Erika Kristina Incerpi (2015)
The Acute Respiratory Distress Syndrome (ARDS) and the Acute Lung Injury (ALI) remain as important causes of morbidity and mortality in patients with sepsis. Understanding the pathophysiology mechanisms of ARDS/ALI is essential to advance in therapeutic modalities. The use of glucocorticoids (GC) has been proposed for the treatment of ARDS/ALI, but with controversial results. The aim of this study was to evaluate the influence of GC on the parameters: corticosterone (CCT) plasma levels, immunoreactive area to GC receptors (GR) in the lung, respiratory mechanics data, lung morphometry, myeloperoxidase activity (MPO) and hydrogen peroxide levels (H2O2) in lung tissue of rats with ALI induced by CLP (Cecal Ligation and Puncture). 144 rats (250-300g) randomly divided into Naïve, Sham and CLP groups (n = 8 / group) were used. In Naïve group, the animals did not suffer any procedure or treatment. In Sham group, rats had the cecum exposed and were pretreated with saline solution an hour prior to surgery. In CLP group, animals had the cecum exposed and drilled, and were divided into three groups according to previous treatments performed an hour before surgery: CLP sal (equivalent volume of saline in 0.9% NaCl i.p.); CLP met (metyrapone 50 mg.kg-1 i.p.); CLP dex (dexamethasone 0.5 mg.kg-1 i.p.). The animals were anesthetized, tracheotomized and coupled to a ventilator for respiratory mechanics evaluation, followed by removal of the lungs for histomorphometric analysis and GR immunoreactive area, 6 and 24 hours after surgery. A different experiment was carried out with the same groups for corticosterone (CCT) plasma measurements, followed by removal of the lungs for biochemical measurements. The met increased tissue damping (Gtis) and hysteresivity (ƞ), inflammatory cells percentage, alveolar collapse area and MPO activity, similar to CLP sal. However, met reduced CCT levels and increased H2O2 levels as compared to the CLP sal, and increased risk of animals’ death. The dex reduced CCT levels and prevented inflammation and pulmonary oxidative stress. Besides, it prevented alveolar collapse, improving Gtis and ƞ, compared to CLP sal. The results showed that the different levels of plasma CCT, observed in septic animals, with exception of those pre-treated with dex, were not able to prevent the morphological and functional and inflammatory changes of the ALI; although there was an increase in GR sensitivity in met pre-treated animals, there was no protection against the installation of ALI; abnormalities in respiratory mechanics parameters found in animals pretreated with sal and met demonstrate that sepsis affects pulmonary function; increased MPO activity in lung tissue observed in septic animals, with exception of those pre-treated with dex, correlated with the increase in pulmonary neutrophils; increased H2O2 levels in lung tissues occurred in animals pretreated with met and may have been influenced by basal levels of CCT.